2018
DOI: 10.1002/path.5143
|View full text |Cite
|
Sign up to set email alerts
|

FGFR3 mutation increases bladder tumourigenesis by suppressing acute inflammation

Abstract: Recent studies of muscle-invasive bladder cancer show that FGFR3 mutations are generally found in a luminal papillary tumour subtype that is characterised by better survival than other molecular subtypes. To better understand the role of FGFR3 in invasive bladder cancer, we examined the process of tumour development induced by the tobacco carcinogen OH-BBN in genetically engineered models that express mutationally activated FGFR3 S249C or FGFR3 K644E in the urothelium. Both occurrence and progression of OH-BBN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 58 publications
5
27
0
Order By: Relevance
“…Inflammatory response was recently described in a similar BBN mouse model where acute response via neutrophils was shown to be dependent on FGFR3 signaling in a study by Foth et al In agreement with them, we observe similar histological changes at 2 weeks, however, at 20 weeks we observe a slightly more advanced tumor stage, which is probably due to a 2-week longer BBN treatment. When compared to an acute 2-week response, they demonstrate a decrease in neutrophil infiltration, after a 10 week-BBN treatment, which is in accordance with an overall decrease in inflammatory response described in our study [36]. Our histological findings are further supported by a decrease in the expression of major inflammatory cytokines and chemokines that are well-described drivers in the setups of acute and chronic inflammation.…”
Section: Discussionsupporting
confidence: 91%
“…Inflammatory response was recently described in a similar BBN mouse model where acute response via neutrophils was shown to be dependent on FGFR3 signaling in a study by Foth et al In agreement with them, we observe similar histological changes at 2 weeks, however, at 20 weeks we observe a slightly more advanced tumor stage, which is probably due to a 2-week longer BBN treatment. When compared to an acute 2-week response, they demonstrate a decrease in neutrophil infiltration, after a 10 week-BBN treatment, which is in accordance with an overall decrease in inflammatory response described in our study [36]. Our histological findings are further supported by a decrease in the expression of major inflammatory cytokines and chemokines that are well-described drivers in the setups of acute and chronic inflammation.…”
Section: Discussionsupporting
confidence: 91%
“…In telomerase-immortalized human urothelial cells (TERT-NHUC) expressing the FGFR3–TACC3 fusion gene, a point mutation in FGFR3 (S249C) activates the MAPK pathway and phospholipase cγ1 (PLCγ1), and induces PLCγ1-dependent overgrowth at the confluence ( 28 , 29 ). At the same time, other studies have shown that a FGFR3 mutation suppressed acute inflammation, causing immune cells (mainly neutrophils) to behave aberrantly in tumors, thereby causing tumor progression ( 30 ). The high-frequency mutations of FGFR3 in the C3 and C4 subtypes are likely to be the cause of poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies also showed the potential roles of FGFR3 in the regulation of inflammatory response under certain conditions. FGFR3 mutation could increase tumourigenesis by suppressing acute inflammation 19. Moreover, fibroblast growth factor 9 (FGF9), a high-affinity ligand of FGFR3, could decrease monocyte infiltration and increase M2 macrophage differentiation in the post-myocardial infarction diabetic heart model 20.…”
Section: Introductionmentioning
confidence: 99%